1996
DOI: 10.1128/jvi.70.7.4714-4723.1996
|View full text |Cite
|
Sign up to set email alerts
|

Cellular factors controlling the activity of woodchuck hepatitis virus enhancer II

Abstract: Woodchuck hepatitis virus (WHV) efficiently induces hepatocellular carcinoma in chronically infected hosts. A key step in hepatocarcinogenesis by WHV is insertional activation of the cellular N-myc gene by integrated viral DNA. WHV enhancer II (En II) is the major cis-acting element involved in this activation. Here we characterize this viral enhancer element and define the cellular factors involved in its activity. WHV En II activity is strongly liver specific and maps to an 88-nucleotide DNA segment (nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…Mapping studies have confirmed that WHV contains promoters analogous to the major HBV promoters (2,29). Recent studies have shown that WHV enhancer II is a strongly liver-specific enhancer that regulates the production of pregenomic RNAs, which is an important ratelimiting step of hepadnavirus replication (6,32). Surprisingly, the WHV region homologous to HBV enhancer I lacks enhancer activity in the three human liver cell lines tested (2,6,31).…”
mentioning
confidence: 95%
“…Mapping studies have confirmed that WHV contains promoters analogous to the major HBV promoters (2,29). Recent studies have shown that WHV enhancer II is a strongly liver-specific enhancer that regulates the production of pregenomic RNAs, which is an important ratelimiting step of hepadnavirus replication (6,32). Surprisingly, the WHV region homologous to HBV enhancer I lacks enhancer activity in the three human liver cell lines tested (2,6,31).…”
mentioning
confidence: 95%
“…Our studies of viral DNA sequences in N-myc2 activation suggested that the region corresponding to HBV EnII played a major role in the activation (22). Accordingly, we and others have mapped and characterized EnII in WHV (3,23). The activity of WHV EnII maps to an 88-nucleotide DNA fragment (nucleotides 1772 to 1859) upstream from the transcription initiation site of pgRNA.…”
mentioning
confidence: 79%
“…, and EnIIABC(Ϫ)E1bCAT were constructed by cloning the insert fragments of pW1697-1919WT, pW1697-1919IIA(Ϫ), pW1697-1919IIB(Ϫ), pW1697-1919IIC (Ϫ), pW1697-1919IIAB(Ϫ), pW1697-1919IIAC(Ϫ), pW1697-1919IIBC(Ϫ) and pW1697-1919IIABC(Ϫ) into the XhoI and XbaI sites in E1bCAT, which has been described elsewhere (23).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations